A review on the radiological protection materiality in environmental sustainability reports (Brazilian Journal of Radiation Sciences (BJRS), 2023)
Materiality should be used as a strategic business tool, with implications beyond social, economic, and environmental responsibility in sustainability reporting. Organizations can benefit by incorporate materiality into their existing economic processes, creating a broader approach and ensuring strategies with significant social and environmental topics. This provides stakeholder engagement; prioritizes financial resources for sustainability; develops new business; identifies climate change issues; among others. In this context, aim this study was to present a review the materiality related to radiologic protection in organizational sustainability reports. The results show that radiologic protection is considered in several topics in the organizational sustainability reports evaluated, represented from issues occupational health and safety, environmental assessment suppliers, environmental compliance, local communities, and waste management. It was concluded that, in preparing the materiality matrix, it is necessary to have the methods defined advance to grant them to be reproduced and periodically reviewed. This will allow to demonstrate the sustainability evolution and its alignment with the organizations' strategies.